Prediction of PVT Properties of a Sudanese Crude Oil (Block 3 and Block 7 as a Case Study) (University of Khartoum Engineering Journal, 2022)
Pressure, volume and temperature (PVT) data is extensively used in the design of oil production andtransportation facilities. The purpose of this study is to predict PVT properties for a Sudanese crude oil atpressures above boiling point pressure using Equations of State (EOSs). Eight of the most widely known EOSsare used; namely Patel-Teja (PT), Peng-Robinson (PR), Modified Peng-Robenson (MPR), Schmidt-Wenzel (SW),Harmens-Knapp (HK), Van Der Waal (VDW), Soave- Redlich-Kwong (SRK) and Lawal-Lake-Silberberg (LLS).For the calculation of PVT from EOSs a computer code is written using MATLAB software. To validate theprediction procedure, experimental PVT is obtained from the Ministry of Petroleum, Sudan. It represents eight (8)crude oil samples compromising 112 data points of constant mass expansion (CME) test at pressure above theboiling point.